Supplementing dried distillers grains with solubles to heavy yearling stocker cattle grazing native tallgrass pastures during late summer and fall improves animal performance and carcass characteristics - Stickel, A.; Houser, Terry A.; Olson, K. C.; Gerlach, B.; Goehring, B.; Pacheco, A.; Macek, M.; Parsons, G.; Miller, K.; Thompson, L.K.; Dikeman, Michael E.; Unruh, John A.; et al. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Grazing stocker cattle on low-quality forages is a common practice in Kansas; however, animal performance typically is modest. Due to the increasing availability of ethanol co-products, producers may be able to use dried distillers grains with solubles (DDGS) as a protein source to help increase body weight of stocker cattle grazing native tallgrass pastures during the late summer and fall. Therefore, the purpose of this research was to investigate the impact of feeding DDGS to heavy stocker cattle during late summer and fall and to document its effects on animal performance and subsequent carcass characteristics.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Dried distillers grains; Stocker cattle; Performance; Carcass characteristics